Infraestrutura e desenvolvimento urbano no município de Cariús-CE: análise do sistema de saneamento básico - Santos Neto, Augusto Albuquerque (Universidade Federal Rural do Semi-Árido, 2017)
It is essential to build sanitation systems that serve the population, as well as contributing to urban cleaning, also avoiding problems for the health and well-being of the population. This study aims to make a technical and theoretical study on the infrastructure and urban development facing the problems arising from the lack of basic sanitation and its development in the city of Cariús-CE. The methodology used was based on the analysis of empirical and theoretical data, through the use of free software, Google Maps, subsidized by the field trip with a view to achieving the proposed objectives. After analyzing data, documents and information gathered with the applied methodology, it was possible to perceive some deficiencies regarding the service to the population by this system, since starting from the assumption of the population increase and the disordered expansion of the urban areas, this development is not accompanied by the Implementation of effective basic sanitation systems.
Keywords: Saneamento Básico; Basic Sanitation; Desenvolvimento Urbano; Urban Development; Cariús; Cariús; Saúde; Health; Infraestrutura Urbana; Urban Infrastructure; CIENCIAS EXATAS E DA TERRA::CIENCIA E TECNOLOGIA